New opportunities for software reuse : 17th International Conference, ICSR 2018, Madrid, Spain, May 21-23, 2018, Proceedings /: 17th International Conference, ICSR 2018, Madrid, Spain, May 21-23, 2018, Proceedings. (2018) - Unknown
No abstract available